Model polymers with dimethylamine and sulfozwitterionic end-groups. Synthesis and self assembly in solution and in bulk - Hadjichristidis, Nikos (Kovine zlitine tehnologije, 1997)
The dilute solution and bulk properties of a variety of well-defined polymers of different architectures (linear homopolymers, diblock and triblock copolymers and star homopolymers) having dimethylamine and sulfobetaine end groups mainly synthesized in our laboratory are reviewed. The end functionalized polymers were synthesized by means of anionic polymerisation high vacuum techniques, using 3-dimethylaminopropyl-lithium as initiator for the introduction of the dimethylamine group at the chain end. This group was converted to sulphozwitterionic by reaction with cyclopropanesultone. Extensive molecular characterization proved the high homogeneity of these model materials. Their aggregation properties in dilute solutions, of solvents of different polarity and selectivity towards different parts of the molecules, were studied by viscometry, static and dynamic light scattering. The ?$ω$?-functionalized polystyrenes and the block copolymers of styrene have a much lower degree of association, than the homopolydienes, probably due to the polarizability of the phenyl group. The bulk properties of end-functionalized homopolymers and diblocks were studied by SAXS, rheology and dielectric spectroscopy revealing new features of self organisation at this low ionic content and extraordinary phase behaviour at high temperatures. The adsorption behaviour of stars with different number of functionalized arms in dilute solutions was also investigated by ellipsometry showing different behaviour compared to linear polymers.
Keywords: polimeri; struktura; polimerizacija; karakterizacija